PENINGKATAN HASIL BELAJAR SISWA MATERI KELILING DAN LUAS SEGITIGA DENGAN METODE INKUIRI - Gusti Ngurah Wijana (FKIP Universitas Jember, 2018)
In delivering subject material, teacher usually uses lecture method. Impact of this problem is less satisfactory student learning outcomes, indicated by amount of students who get score below Minimum Completeness Criteria, which is 70. The purpose of this research was to find students learning outcomes. A total of 38 students were involved in this study using Classroom Action Research (CAR) method which carried out in 2 cycles. Instument that used are test instrument and observation paper. Data analysis technique used in this research is Comparative Descriptive, by comparing data of learning outcomes in cycle I and cycle II. Based on test result in the first cycle, the average value is 69.86 with classical percentage of 66.67% with 12 of 36 students who had not completed their studies, in second cycle the average value is 80.56 with classical percentage 88.89% with 4 of 36 students who had not completed their studies.